Problems in the Translation of Phraseologisms in Bilingual Dictionaries Spanish-Chinese / Chinese-Spanish (Sinología hispánica. China Studies Review, 2019)
The phraseology is part of the linguistic studies on phrases, proverbs, idioms, proverbs and other units of syntax totally or partially fixed. It is the reflection of a certain tradition and idiosyncrasy of society. The native speaker recognizes the phraseological units in the praxis of speech without difficulty. However, because of their idiomaticity and the sociocultural divergence between two linguistic communities, Spanish sayings and expressions cannot always be understood by the Chinese speakers. Students of Spanish as a foreign language have difficulty recognizing the non-literal meaning of an expression, the use of this type of expression in language teachingdevelops communicative competence, linguisticscompetence, sociolinguistics and pragmaticscompetence. Then, when producing a bilingualdictionary, it is not enough to translate it into thetarget language, but rather to contrast the twolanguages in order to inform non-native speakersof unknown elements, such as historical andcultural backgrounds, uses, and their frequencyof application, variants, etc.